Vyhodnotenie malakofauny z náplavov Neresnice (stredné Slovensko) - Marek Čiliak; Jozef Šteffek (Malacologica Bohemoslovaca, 2011)
Sampling of flood debris deposits can be useful method in insufficiently surveyed areas. This sampling method also allows us to detect the presence of rare and endangered species in the study area. We studied flood debris along the Neresnica River to gather data on mollusc fauna of the Pliešovská Kotlina basin and the Javorie Mts. (Central Slovakia). In spring 2010, samples of flood debris were taken at three sites along the river. Molluscan thanatocoenoses were composed of 68 species (56 terrestrial and 12 aquatic ones). The most notable records were two subterranean species – Lucilla scintilla and L. singleyana, and also the species of nature conservation interest – Vertigo angustior. We found representatives of all ecological groups of molluscs, which provide the evidence of ecosystem diversity in various habitats along the river. We documented that the land use of the studied drainage basin was only partially reflected by the structure of mollusc assemblages from flood deposits.